Emerging arboviruses (dengue, chikungunya, and Zika) in Southeastern Mexico: influence of socio-environmental determinants on knowledge and practices - Roberta Causa; Héctor Ochoa-; Ariane Dor; Fernando Rodríguez-León; Roberto Solís-Hernández; Ana Laura Pacheco-Soriano (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: The proliferation of arboviruses and their vectors is influenced by a complex interplay between vector, environment and human behaviors. The aim of this work is to analyze the influence of socio-environmental determinants on knowledge and practices regarding arboviruses transmission, among the residents of three communities on the southern border of Mexico. Between June 2017 and August 2018, a set of 149 households from three communities of Tapachula (Chiapas) and Villahermosa (Tabasco) were covered. This study consists of the application of a community prevention project. Different surveys and methodological approaches were used. Associations between socio-environmental determinants and knowledge and practices for arboviruses transmission control were estimated by odds ratio. Logistic regression and qualitative techniques were used. Although around 75% of households had an adequate knowledge about arboviruses' origin and transmission, only 30% of them adopted adequate practices. Domestic risk practices were associated with serious deficiencies in water and sanitation services. Furthermore, a perception of greater risk and difficulty in complying with preventive measures were detected. An adequate knowledge does not necessarily lead to adequate prevention practices. Intermediate social determinants influence on the persistence of risk behaviors for arboviruses proliferation. Addressing such related aspects requires the achievement of an effective and sustainable vector management.